THE IMPLEMENTATION OF PREZI APPLICATION IN IMPROVING WRITING SKILL OF THE ELEVEN GRADE STUDENTS OF MAS AL-AMIN - Syahputri, Andi Anggi Aprilia; Indahyanti, Rizka; Imran, Muhammad Chairil (ADHILINGUA: Journal of Language Education, Lilnguistics and Literature, 2025)
Writing skills remain a critical challenge for non-native English speakers, particularly in organizing ideas, vocabulary usage, and grammar mastery. Technology integration in language education shows promising results in enhancing student engagement and learning outcomes, addressing the need for innovative teaching methods. This study investigates difficulties faced by eleventh-grade students at MAS AL-AMIN in developing English writing skills. Specific challenges include inadequate idea organization, limited vocabulary application, and insufficient grammar mastery. The research determines whether Prezi application implementation can effectively address these difficulties as an interactive visual learning tool. An experimental design involved 38 eleventh-grade students divided into experimental (Prezi-based instruction) and control (conventional methods). Data collection included pre-tests, post-tests, and questionnaires. Statistical analysis used SPSS 25 with descriptive statistics and independent sample t-tests. Findings demonstrated statistically significant improvement in the experimental group's writing performance. The experimental group achieved 9.14 points higher average gain scores than the control group (p < 0.05), showing enhanced grammar, vocabulary, and comprehension abilities. Questionnaire results revealed increased student motivation and interest using Prezi.  This research contributes empirical evidence for interactive presentation tools' effectiveness in writing instruction. Prezi serves as a valuable alternative medium for English instruction, offering practical implications for educators integrating technology and theoretical contributions to understanding visual learning tools in language acquisition.